2020
DOI: 10.21203/rs.3.rs-128147/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Composition of Leaves and Hull from Pistacia Vera L. an Evaluation of Phenolic Content and Antioxidant Properties of their Extracts

Abstract: The pistachio industry in Tunisia generates a high amount of waste every year due to the large pistachio production. This, together with the good properties of the compounds that can be extracted from these by-products, makes it necessary a comprehensive study of their potential. Because of that, the aim of this work was to analyze the chemical characterization of male and female leaves and hull of Pistacia vera L. and their ethanol-water extracts. With that purpose, the total phenolic and flavonoid contents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…Garavand et al [40] who reported that the TPC of aqueous extracts was 179 mg GAE/g. On the other hand, our TPC results were lower than those found by Elakremi et al [41] who reported that the TPC of ethanol-water extracts of pistachio hull, collected from Gafsa (Tunisia), was 218 mg GAE/g. Nevertheless, our data are higher than those reported by Rajaei et al [19], who compared the effect of eleven different solvents and found that water and acetonitrile with 49.32 and 6.22 mg GAE/g sample were the best and the worst solvents in the extraction of TPC, respectively.…”
Section: Phytochemical Contentcontrasting
confidence: 99%
“…Garavand et al [40] who reported that the TPC of aqueous extracts was 179 mg GAE/g. On the other hand, our TPC results were lower than those found by Elakremi et al [41] who reported that the TPC of ethanol-water extracts of pistachio hull, collected from Gafsa (Tunisia), was 218 mg GAE/g. Nevertheless, our data are higher than those reported by Rajaei et al [19], who compared the effect of eleven different solvents and found that water and acetonitrile with 49.32 and 6.22 mg GAE/g sample were the best and the worst solvents in the extraction of TPC, respectively.…”
Section: Phytochemical Contentcontrasting
confidence: 99%
“…Numerous studies in the literature explore the extraction, characterization, and effects of antioxidant compounds sourced from diverse origins. For instance, research has examined antioxidant compounds derived from almonds (Sarwar et al., 2012 ; Valdés et al., 2022 ), peanut shells (Adhikari et al., 2019 ), pistachio leaves and hulls (Elakremi et al., 2020 ; Gharibi et al., 2023 ), and walnut green husks (Fernández‐Agulló et al., 2013 ; Oliveira et al., 2008 ). Additionally, investigations have been conducted on enzyme inhibitory activities associated with peanut shell skin (Kilic et al., 2016 ), cytotoxic effects of peanut hulls on cancer cell lines including HeLa, MCF‐7, OE‐33, and ACC‐201 (Karaoglu & Tarhan, 2022 ; Seifaddinipour et al., 2018 ), and the impact of green walnut husk extracts on the proliferation and migration of gastric cancer cells (Zhang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of phytomolecules-based synthesis of NPs is of great interest as this process is relatively easy, rapid and does not require a special reaction environment [16]. For this reason, to utilize the benefit of the phytochemicals, the extracts of Punica granatum (pomegranate) peel, seeds and fruits [17], ephedra [18] and pistachio leaves [19] were used in the synthesis process in this study.…”
Section: Introductionmentioning
confidence: 99%